2023
DOI: 10.1021/acs.energyfuels.2c04138
|View full text |Cite
|
Sign up to set email alerts
|

Composite Metal–Organic Framework-Derived NiCoP/MoS2 Heterostructure with Superior Electrocatalytic Credentials for Urea and Methanol Oxidation

Abstract: The urea oxidation reaction (UOR) and methanol oxidation reaction (MOR) are the most practical alternative counter-reactions to the hydrogen evolution reaction in the overall electrochemical water splitting process. The thermodynamic gains in terms of lower water-splitting potentials compared to the oxygen evolution reaction (OER) can be cashed in if the kinetics of the UOR and MOR can suitably be controlled. This has called for the development of suitable cost-effective and non-precious catalysts for the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…Hence, P atoms play a role in adsorption and desorption, improving activity. [52] With these considerations, phosphides and sulfides hetero-structures such as Ni 2 P/Ni 0.96 S, [53] CoP nanoplates with Ni 3 S 2 nanospheres, [54] Ni 3 S 2 @NiP 2 , [55] NiCoP@MoS 2 , [56] Nickel iron phosphosulfide, [57] etc. are been developed and had a contribution in performing urea electrolysis.…”
Section: Hetero-interface Formationmentioning
confidence: 99%
“…Hence, P atoms play a role in adsorption and desorption, improving activity. [52] With these considerations, phosphides and sulfides hetero-structures such as Ni 2 P/Ni 0.96 S, [53] CoP nanoplates with Ni 3 S 2 nanospheres, [54] Ni 3 S 2 @NiP 2 , [55] NiCoP@MoS 2 , [56] Nickel iron phosphosulfide, [57] etc. are been developed and had a contribution in performing urea electrolysis.…”
Section: Hetero-interface Formationmentioning
confidence: 99%
“…During the anodic potential sweep, the in situ converted metal oxyhydroxide, MOOH (M = Ni, Co, Mn), is the active species for the UOR. Ni based catalysts, like Ni MOF, mesoporous Ni–P, Ni 2 P, NiO, , Ni@NiO nanoparticles, alloyed Ni nanoparticles like Ni–Rh, Ni–Co, and Ni–Mn, Ni sulfide, Ni based bimetallic oxide/hydroxides such as NiMoO 4 , , NiCo 2 O 4 , Ni 0.9 Fe 0.1 O x , Cu:α-Ni­(OH) 2 , and NiMn–OH, NiCo layered double hydroxide, and Ni based heterostructures like NiCoP/MoS 2 , were employed for the UOR. Zhang et al reported NiMo nanotubes as a bifunctional catalyst (Figure A–D) to catalyze the HER and UOR in alkaline electrolyte.…”
Section: Hybrid Water Electrolysismentioning
confidence: 99%
“…Methanol is a typical alcohol, which can be electrochemically oxidized into CO 2 . Urea is a representative and simple amine, which can be oxidized to CO 2 and N 2 at the anode with H 2 forming at the cathode in a combined system. In addition, some inorganic reactions can also be used as the institute of OER to combine with HER for energy effective H 2 production. NO is a typical harmful pollutant, which can be oxidized into nitrate in the combined systems with a potential of ∼1.07 V .…”
Section: Her Coupled With Electrochemical Oxidation Reactionsmentioning
confidence: 99%